The cubic-plus-association equation of state for hydrofluorocarbons, hydrofluoroolefins, and their binary mixtures. (14th December 2019) - Yang, Fufang; Chu, Qingfu; Liu, Qiang; Duan, Yuanyuan; Yang, Zhen
Graphical abstract: Highlights: Accounted for the CF⋯H weak hydrogen bond in thermodynamic property modeling. Tailored the CPA EoS and fitting procedure for HFCs, HFOs, and binary mixtures. Accurately reproduced VLE and density for 15 pure fluids and 40 binary mixtures. Evaluated the qualitative behavior of the association term. Abstract: Hydrofluorocarbons, hydrofluoroolefins, and their mixtures are widely used as working fluids in energy systems. Weak hydrogen bond exists in these fluids and thus contribute to their thermodynamic properties. In this work, we account for the contribution of the weak hydrogen bond by tailoring the cubic-plus-association (CPA) equation of state (EoS) and its parameter fitting procedure. Overfitting to the liquid properties is avoided by introducing the saturated vapor density into the fitting objective function. The EoS is extended to binary mixtures using the van der Waals mixing rules and Elliot combining rule in which process solving the cross-association fraction is reduced from an equation set consisting of 4 nonlinear equations to a single nonlinear equation. The performance of the present model is investigated in terms of the vapor-liquid equilibria (VLE) and volumetric properties of 15 pure fluids and 40 binary mixtures using fitted and zero binary interaction parameter, and is compared with the reference data, a CPA EoS that uses the traditional parameter fitting procedure, the Soave-Redlich-Kwong (SRK) EoS, and a volume-translated SRK EoS. The present model (including the EoS and fitting procedure) accurately reproduces the vapor pressure, density, and second virial coefficient for the pure fluids and binary mixtures, and is the only valid model among the investigated models for both the VLE and the volumetric properties in both liquid and vapor phases. The contribution of the association term to the pressure is also shown in the temperature-density diagram, presenting a similar behavior as that in water in which the effect of the hydrogen bond is comparatively more pronounced.